THE PASSAGE OF COLLOIDAL PARTICLES ACROSS THE DERMAL CAPILLARY WALL UNDER THE INFLUENCE OF HISTAMINE - John F. Alksne (1959)
Quarterly Journal of Experimental Physiology and Cognate Medical SciencesVolume 44, Issue 1 p. 51-66 ArticleFree Access THE PASSAGE OF COLLOIDAL PARTICLES ACROSS THE DERMAL CAPILLARY WALL UNDER THE INFLUENCE OF HISTAMINE John F. Alksne, John F. Alksne The Department of Anatomy, University of Washington, Seattle 5, Washington, U.S.A.Search for more papers by this author John F. Alksne, John F. Alksne The Department of Anatomy, University of Washington, Seattle 5, Washington, U.S.A.Search for more papers by this author First published: 22 January 1959 https://doi.org/10.1113/expphysiol.1959.sp001376Citations: 60 The author wishes to thank Professor H. Stanley Bennett, who suggested this study and who assisted in some of the early experiments [Alksne and Bennett, 1956], for his direction and encouragement. AboutPDF ToolsRequest permissionExport citationAdd to favoritesTrack citation ShareShare Give accessShare full text accessShare full-text accessPlease review our Terms and Conditions of Use and check box below to share full-text version of article.I have read and accept the Wiley Online Library Terms and Conditions of UseShareable LinkUse the link below to share a full-text version of this article with your friends and colleagues. Learn more.Copy URL Share a linkShare onFacebookTwitterLinked InRedditWechat Citing Literature Volume44, Issue1January 22, 1959Pages 51-66 RelatedInformation